(untitled) (Heritage, 2026)
The aim of this paper is to provide an overview of the key features of legal language, both in legal studies and in linguistics, especially within functional stylistics, where legal language is studied as a specific subtype of the administrative-legal style. Building upon our 2021 research on the study of legal language in Serbia, we approach law as a phenomenon that is primarily linguistic and realized through language. For linguists, particularly relevant are the distinctions between legal provisions and legal norms, the deep structure of legal norms, law as a semiotic system, the ideologization of legal language, as well as the ways in which language and legal norms shape society. The paper highlights the most important characteristics of the administrative-legal style, especially the legislative-legal substyle, within which legal language is predominantly realized. Emphasis is placed on the simultaneous precision and vagueness of legal language, its redundancy, intertextuality, and other relevant features. In the conclusion, the paper outlines potential directions for further research, advocating for cooperation between legal scholars and linguists, while taking into account the inherent features of legal language.